Les droits sexuels des personnes handicapées: réflexion sur le développement du droit international - Mona Paré (Genre, Sexualité et Société, 2018)
Interest in the sexuality of persons with disabilities is growing and research improves our understanding of issues in this regard. This leads us to a reflection on the definition of sexual rights in international law, and the way in which sexual rights of persons with disabilities are understood. Examining existing norms leads to the conclusion that despite developments in this area, sexual rights remain largely limited to the field of health, and this has not changed with the adoption of the Convention on the Rights of Persons with Disabilities (CRPD). The limited claims related to these rights during the negotiations of the CRPD is surprising given the significant participation of persons with disabilities. Yet, despite the lack of clarification in relation to the sexual rights of persons with disabilities in the convention, the practice of interpretation of law remains a way to develop international law in this field, particularly through the evolving concept of non-discrimination.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; approches et analyses; capacitisme; cours; discipline; droit; droit des personnes en situation de handicap; droit international; histoire et politique; militance; premier cycle; périodes historiques; ressource en ligne; santé; science politique et droit; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Des hommes aux prises avec l’agencement valido-viril dans L'expérience handie : handicap et virilité - Dufour, Pierre; Welzer-Lang, Daniel (L'expérience handie : handicap et virilité, 2013)
Parler de handicap, investir le champ du handicap conduit à questionner les manières de porter le geste, d'agir, de se mouvoir, que chacun d'entre nous a coutume de tenir pour neutres et ordinaires. Car comment construit-on sa virilité quand le corps ne correspond pas au standard, quand la force ou le muscle fait défaut ? Comment parle-t-on de soi, lorsqu'on est en situation de handicap ? Comment appréhende-t-on son expérience, lorsque certains gestes ne peuvent se faire en autonomie, et nécessitent une coréalisation, l'aide, la coopération de l'autre ? A travers des entretiens non directifs d'hommes "handis", comme ils se définissent eux-mêmes, complétés par de l'observation participante, Pierre Dufour, lui-même en fauteuil, dénoue le discours qui sous-tend la situation de handicap, le regard que l'on porte sur soi, sur sa virilité, sur sa capacité à s'affranchir des standards et d'un vocabulaire issus d'un agencement du monde "valido-viril" qui ne sont d'aucune utilité pour décrire son quotidien : parle-t-on d'un corps qui rampe sur la plage pour aller se baigner ? Qui fait la "brouette" pour monter un escalier ? Quelle place ambiguë le sport "handi" tient-il vraiment dans ce rapport au corps ? On questionne rarement les normes et les valeurs issues des modalités d'être valides. Or comment soutenir que disposer d'un corps muni de bras et de jambes, mobiles, allant par deux, n'induirait aucune norme, n'orienterait en rien les descriptions ? Croisant les thèmes du handicap et du genre, l'auteur interroge à la fois les pratiques d'hommes se déplaçant en fauteuil roulant et le stock social des discours possibles sur la diversité corporelle. Par son approche originale, cet ouvrage apporte un éclairage peu courant, et notamment sur le thème de l'assistance sexuelle.
Section: 1 v. (147 p.) : couv. en illustrations ; 21 cm
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; capacitisme; corps; cours; discipline; europe; france; inégalités; premier cycle; privilèges; périodes historiques; régions géographiques; sciences humaines; sexualité; soc3113; sociologie; systèmes d'oppressions; thématiques